PERAN KEPALA SEKOLAH DALAM MEWUJUDKAN AKUNTABILITAS PEMBIAYAAN PENDIDIKAN DI MADRASAH - Corina Dwi Cahya Ningrum Jiwantoro; Muhamad Iqbal Firdaus; Rian Adriana As'ari Mukti; Shalha Nurul Afifah; Dodo Murtado (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational financing accountability is a critical aspect of madrasah management that requires strong leadership from the principal. This study aims to analyze the role of madrasah principals in realizing educational financing accountability, encompassing planning, implementation, reporting, and oversight functions. This research employs a qualitative descriptive approach with a case study design conducted at MTs Yasta Bunter Sumedang. Data were collected through in-depth interviews, observation, and documentation studies. Informants included the principal, treasurer, school committee members, senior teachers, and the Ministry of Religious Affairs supervisor. Data analysis followed the Miles, Huberman, and Saldana interactive model. The results show that the principal plays a central role in: (1) planning the school budget through participatory RKAM preparation; (2) overseeing fund disbursement in accordance with BOS/BOP technical guidelines; (3) ensuring transparent financial reporting via RKAM; and (4) conducting internal supervision and coordinating with external supervisors. Supporting factors include competent treasurers and clear regulations, while inhibiting factors include limited digital literacy of principals and unstable internet connectivity. The study concludes that the principal's accountability role is significantly influenced by leadership commitment, stakeholder participation, and a digital reporting system. Recommendations are directed at the Ministry of Religious Affairs to provide regular training and technical assistance to madrasah principals.